INSEN as Part and Propellant of the Nuclear Security Regime: An Insider’s View - Şebnem Udum (International Journal of Nuclear Security, 2020)
This short piece presents an insider’s view of the International Nuclear Security Education Network (INSEN), and shows that the Network is not only a part of the evolving nuclear security regime, but also it drives the regime forward through academic research, teaching and cooperation which are facilitated by the meetings at the IAEA and social activities in extracurricular time in Vienna.
Keywords: INSEN; nuclear security; regime